2005
DOI: 10.1016/j.femsle.2005.02.025
|View full text |Cite
|
Sign up to set email alerts
|

AvrPtoB: A bacterial type III effector that both elicits and suppresses programmed cell death associated with plant immunity

Abstract: Pseudomonas syringae pv. tomato DC3000 is a model pathogen for studying the molecular basis of plant immunity and disease susceptibility in tomato and Arabidopsis. DC3000 uses a type III secretion system to inject effector proteins into the plant cell. Type III effectors are thought to promote bacterial virulence by suppressing plant defenses and enhancing access to nutrients trapped in the plant cell. The AvrPtoB type III effector elicits immunity-associated programmed cell death (PCD) when expressed in tomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 49 publications
3
35
0
3
Order By: Relevance
“…Data sets marked with an asterisk are significantly different from the control (water-treated leaves followed by 8004 infection and water-pretreated leaves followed by 8397 or 8396 infections) as assessed by the Student's t test. Martin, 2004Martin, , 2005Alfano and Collmer, 2004;Nomura et al, 2005). It has recently been shown that the P. syringae type III secretion system down-regulates the expression of a set of Arabidopsis genes encoding putatively secreted cell wall and defense proteins in a salicylic acid-independent manner (Hauck et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Data sets marked with an asterisk are significantly different from the control (water-treated leaves followed by 8004 infection and water-pretreated leaves followed by 8397 or 8396 infections) as assessed by the Student's t test. Martin, 2004Martin, , 2005Alfano and Collmer, 2004;Nomura et al, 2005). It has recently been shown that the P. syringae type III secretion system down-regulates the expression of a set of Arabidopsis genes encoding putatively secreted cell wall and defense proteins in a salicylic acid-independent manner (Hauck et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that an unidentified activity that suppresses basal defences is present in the AvrPtoB N terminus. Some homologues of AvrPtoB only have similarity to the N terminus of AvrPtoB 100,101 , indicating that the N terminus of AvrPtoB has a virulence activity that is independent of the C-terminal anti-PCD activity 102 .…”
Section: Bacterial Suppression Of Hr-based Pcdmentioning
confidence: 99%
“…Prf is monomorphic, at least in the tomato species analysed to date. Pto is the direct target of two unrelated P. syringae effectors, AvrPto and AvrPtoB, each of which contributes to pathogen virulence in pto mutants 102 . It is thus likely that Prf guards Pto (refs 101, 103).…”
mentioning
confidence: 99%